Hydrophilic nickel-carbon catalyst with catalytic hydrolysis performance as well as preparation method and application of hydrophilic nickel-carbon catalyst
By using glucose to prepare hydrophilic activated carbon as a support, a cost-effective nickel carbon catalyst is prepared, which solves the problem of high cost of nickel-based catalysts and achieves efficient catalytic hydrolysis effect in the hydrolysis process of lignite coal.
Patent Information
- Application Number
- CN202411482745.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-08-26
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The high cost of existing nickel-based catalysts limits their wide application in the hydrolysis of lignite, and the cost of traditional precious metal catalysts limits their economic and industrial applications.
Glucose is used as the carbon precursor, hydrophilic activated carbon is prepared as a support by a two-step method, and a hydrophilic nickel carbon catalyst with catalytic hydrolysis performance is prepared by a wet impregnation method to reduce costs and improve catalytic activity.
A cheap, pore-rich nickel carbon catalyst is realized, and can efficiently catalyze the hydrolysis of lignite model compounds under mild conditions, significantly reducing the production cost of the catalyst and improving catalytic activity and reaction efficiency.
Smart Images

Figure CN119303583A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nickel-based catalyst preparation, and in particular to a hydrophilic nickel-carbon catalyst with catalytic hydrolysis performance, a preparation method and application thereof. Background Art
[0002] The aromatic ether bridge bonds in the lignite structure connect the aromatic ring structures into a macromolecular network structure. These oxygen-containing aromatic ring structures are all fine chemicals with high added value. Therefore, if the directional cleavage of the CO ether bond in the lignite macromolecule can be achieved, the macromolecular skeleton can be broken into small molecular substances, realizing the efficient utilization of lignite. Catalytic hydrogenation of lignite and its model compounds causes the aromatic ether CO bond to break, which is considered to be a milder method for depolymerizing lignite. Previous studies have found that the hydrogenation conversion process of lignite model compounds simultaneously undergoes hydrogenolysis, hydrolysis and hydrogenation reactions, which makes the reaction process and mechanism research quite complicated. Compared with traditional hydrogenation and deoxygenation, the hydrolysis reaction uses water as a solvent, is green and environmentally friendly, and has mild reaction conditions, low energy requirements, and good atom economy. It can make full use of the characteristics of lignite rich in organic oxygen to prepare oxygen-containing compounds.
[0003] Researchers have conducted extensive research on precious metal catalysts with Ru, Pd and Pt as active centers. However, the high cost limits the widespread application of precious metal catalysts. From the perspective of economy and future industrialization, it is imperative to design and develop low-cost non-precious metal heterogeneous catalysts. Ni-based catalysts have a catalytic effect comparable to Ru, Pd and Pt in heavy oil hydrogenation, and when Ni is loaded on various carriers, it can effectively break the CO bond and CC bond in the lignite molecular structure. By rationally designing the Ni-based catalytic system, it is possible to achieve the goal of selectively breaking specific bonds in lignite to obtain high value-added chemicals.
[0004] The carrier of the catalyst is an indispensable part of the catalyst, and plays an extremely important role in the catalytic hydrogenolysis and hydrolysis of lignite or its model compound. CN113083308A discloses the application of a nickel-based catalyst with a high specific surface area hydrophilic activated carbon as a carrier in catalytic hydrogenation and hydrolysis, wherein a nickel source is used as a precursor, and a high specific surface area and strongly hydrophilic activated carbon is used as a carrier, and a highly active nickel-based catalyst Ni / AC is synthesized by an impregnation method. The catalyst can efficiently catalyze the hydrogenation and hydrolysis of diphenyl ether under mild conditions when isopropanol is used as a solvent, and obtain more than 20% of the hydrolysis reaction product. However, the carrier used in the catalyst is a commercially purchased hydrophilic activated carbon, which is relatively expensive. Therefore, selecting a cheap precursor material to prepare hydrophilic activated carbon is an important way to reduce the cost of nickel-based catalysts. Summary of the invention
[0005] One of the purposes of the present invention is to provide a method for preparing a hydrophilic nickel-carbon catalyst with catalytic hydrolysis performance, using glucose as a carbon precursor material to prepare hydrophilic activated carbon, thereby reducing the catalyst cost.
[0006] The second object of the present invention is to provide a hydrophilic nickel-carbon catalyst having catalytic hydrolysis performance obtained by the above preparation method.
[0007] The third object of the present invention is to provide the use of the hydrophilic nickel-carbon catalyst in the catalytic hydrogenation and hydrolysis of lignite model compounds.
[0008] To achieve the above purpose, the technical solution adopted by the present invention is as follows: In a first aspect, the present invention provides a method for preparing a hydrophilic nickel-carbon catalyst having catalytic hydrolysis performance, comprising the following steps: In the first step, glucose was used as a precursor and a hydrophilic carrier (HAC) was prepared by a two-step method under an inert atmosphere. Glucose was placed in a tube furnace under an inert atmosphere at 400-900 o C for 2 h; the carbon obtained by carbonization was ground into powder, and then subjected to alkali washing, acid washing, water washing and drying treatment in sequence to obtain a glucose-based carbon material; the glucose-based carbon material was fully mixed with potassium hydroxide in a mass ratio of 1:3, and then the mixture was placed in a tube furnace and heated at 400-900 o C for 2 h; the activated sample was acid-washed, water-washed and dried in sequence to obtain the HAC carrier.
[0009] In the second step, a hydrophilic nickel-carbon catalyst was prepared by wet impregnation. The HAC carrier was added to a nickel salt aqueous solution, ultrasonically dispersed, and then the mixed solution was vacuum impregnated at room temperature for 24 h. The impregnated mixture was dried, then calcined in an inert atmosphere at 450 °C for 2 h, and then reduced in a reducing atmosphere at 450 °C for 2 h to obtain a hydrophilic nickel-carbon catalyst.
[0010] Preferably, in the first step, the carbonization temperature is 600 o C, the activation temperature is 700 o C.
[0011] Preferably, in the second step, the nickel salt is one of nickel nitrate, nickel acetate, nickel sulfate and nickel chloride.
[0012] Preferably, in the second step, the heating rate of the calcination and reduction is maintained at 15 o C / min.
[0013] In a second aspect, the present invention provides a hydrophilic nickel-carbon catalyst having catalytic hydrolysis performance, which is prepared by the above-mentioned preparation method.
[0014] Preferably, the nickel loading in the catalyst is 10 wt.%.
[0015] Hydrophilic activated carbon (HAC) is prepared using cheap, abundant and sustainable glucose as a carbon precursor. It is rich in pores and has a large specific surface area, which can significantly improve the mass transfer process of reactants and solvents, thereby promoting the adsorption and conversion of reaction substrates. The hydrophilic nickel-carbon catalyst prepared by the conventional impregnation method has highly dispersed metallic nickel on the surface of the HAC carrier, and the metal particles have a small particle size and high catalytic activity.
[0016] In a third aspect, the present invention provides a hydrophilic nickel-carbon catalyst that can achieve complete conversion of lignite model compounds under relatively mild conditions.
[0017] The specific application steps include: placing reactants, nickel-carbon catalyst and isopropanol into a reactor, sealing it, and then removing the remaining air by introducing hydrogen; then, pressurizing the reactor with hydrogen to the desired pressure (0.5-3.0 MPa) at room temperature, and then raising the temperature to the desired reaction temperature (120-220 o C) and maintained at a vigorous stirring speed of 800 rpm for a certain period of time (30-150 min). After the experiment, the reaction system was naturally cooled to room temperature and the pressure was released. The reaction mixture was filtered to remove the catalyst, and the obtained organic phase was analyzed by gas chromatography-mass spectrometry and gas chromatography.
[0018] Compared with the prior art, the present invention has the following beneficial effects: 1. Hydrophilic activated carbon prepared with cheap, abundant and sustainable glucose as carbon precursor is selected as the carrier. The nickel-carbon catalyst prepared by conventional impregnation method is rich in pores, large specific surface area, strong hydrophilicity, highly dispersed metal nickel on the carrier surface, small metal particle size, and easy to prepare. 2. The hydrophilic nickel-carbon catalyst provided by the present invention can not only rapidly hydrogenate and hydrolyze diphenyl ether, but also realize complete conversion of derivatives of other lignite model compounds under relatively mild conditions, and can realize efficient catalytic hydrolysis of lignite model compounds into corresponding monocyclic products, which indicates that it has wide applicability. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] FIG1 (a) is an XRD pattern of Ni / HAC-400-400, Ni / HAC-600-700, Ni / HAC-700-700, and Ni / HAC-900-900 catalysts prepared in Example 1 of the present invention; Figure 1 (b) is an XRD pattern of Ni / HAC-400-700, Ni / HAC-500-700, Ni / HAC-600-500, Ni / HAC-600-600, Ni / HAC-600-800, Ni / HAC-800-700, Ni / HAC-800-800, Ni / HAC-500-500, and Ni / HAC-600-400 catalysts prepared in Example 1 of the present invention; Figure 2 is a contact angle diagram of a portion of the Ni / HACs catalyst prepared in Example 1 of the present invention; Figure 3 1 are SEM images of some Ni / HACs catalysts prepared in Example 1 of the present invention; (a) Ni / HAC-400-400, (b) Ni / HAC-600-700, (c) Ni / HAC-700-700, (d) Ni / HAC-900-900, (e) Ni / HAC-400-400, (f) Ni / HAC-600-700, (g) Ni / HAC-700-700, (h) Ni / HAC-900-900, (i) Ni / HAC-400-400, (j) Ni / HAC-600-700, (k) Ni / HAC-700-700 and (l) Ni / HAC-900-900; Figure 4 TEM images of some Ni / HACs catalysts prepared in Example 1 of the present invention; (a) HRTEM images of Ni / HAC-400-400, (b) Ni / HAC-600-700, (c) Ni / HAC-700-700, (d) Ni / HAC-900-900, (e) Ni / HAC-600-700 and (f) EDS layered images of TEM test elements of Ni / HAC-600-700; FIG5 (a) is a graph showing the experimental results of catalytic hydrolysis of diphenyl ether by Ni / HAC-400-400, Ni / HAC-500-500, Ni / HAC-600-600, Ni / HAC-700-700, Ni / HAC-800-800, and Ni / HAC-900-900 prepared in Example 1 of the present invention; 5( b ) is a graph showing the experimental results of catalytic hydrolysis of diphenyl ether by Ni / HAC-400-700, Ni / HAC-500-700, Ni / HAC-600-700, Ni / HAC-700-700, and Ni / HAC-800-700 prepared in Example 1 of the present invention; 5( c ) is a graph showing the experimental results of catalytic hydrolysis of diphenyl ether by Ni / HAC-600-400, Ni / HAC-600-500, Ni / HAC-600-600, Ni / HAC-600-700 and Ni / HAC-600-800 prepared in Example 1 of the present invention; Figure 6 is the effect of reaction temperature on the hydrogenation and hydrolysis of diphenyl ether; Figure 7 is the effect of reaction time on the hydrogenation and hydrolysis of diphenyl ether; Figure 8 It is the effect of reaction pressure on the hydrogenation and hydrolysis of diphenyl ether. DETAILED DESCRIPTION
[0020] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0021] Example 1: Preparation of Catalyst Ni / HAC-600-700 1. Metal loading by wet impregnation method Glucose was used as a precursor to prepare the hydrophilic carrier (HAC) in two steps. 5 g of glucose was used as the carbon source and evenly spread in a nickel boat. The temperature was set at 400-900 °C in an argon atmosphere. o The carbonization of glucose was carried out in a tube furnace in the C range with a fixed heating rate of 10 o C / min, the carbon material obtained after carbonization is ground in a mortar until there is no particle feeling, and then added to 100mL2M sodium hydroxide solution (mainly to remove the intermediate products such as tar acid produced by glucose at high temperature to ensure the purity of the carbon material after carbonization). After stirring for 10 minutes, it is pickled with 100mL2M hydrochloric acid to neutralize the alkali in the solution. Then wash with deionized water until neutral and dry for 12h. The dried carbon material is mixed with the activator KOH powder (sieved with a 100-mesh sieve), the ratio of activator to carbon material is 3:1, and then spread on the nickel boat, and the set temperature is 400-900 in an argon atmosphere. o C range for chemical activation. After the activated carbon material is ground in a mortar until there is no particle feeling, 100mL of 2M hydrochloric acid solution is poured in and stirred for 10min. Then it is washed with deionized water until neutral. Finally, after drying for 12h, the hydrophilic carrier HAC is obtained. The prepared HAC is represented by HAC-XY, where X=400, 500, 600, 700, 800 and 900 represent the carbonization temperature, and Y=400, 500, 600, 700 and 800 represent the activation temperature. HAC-600-700 represents the carrier obtained after GC is carbonized at 600 degrees Celsius for 2 hours and activated at 700 degrees Celsius for 2 hours.
[0022] The Ni / HACs catalyst was synthesized by wet impregnation method. In a typical experiment, 0.5505 g Ni(NO3)2·6H2O was dissolved in 5 mL deionized water in a beaker. After stirring for 2 min, 1 g HACs was added to the aqueous solution and ultrasonicated for 15 min. Then, the mixed solution was kept in a vacuum oven for 24 h. Subsequently, the mixture was heated at 110 °C. o C for 12 h and heated at 450 °C under a flow of argon at 70 mL / min. o C for 2 h, and then calcined at 450 o C and reduced with H2 at the same flow rate for 2 h. In this work, the heating rate for calcination and reduction was kept at 15 o C / min. The nickel loading of all catalysts was 10 wt.%.
[0023] Table 1 Physical structure properties of catalysts a The specific surface area was calculated according to the BET method. b The total pore volume is calculated at a relative pressure of P / P0=0.99 c The average pore size is calculated according to the BJH method. As shown in Table 1, the specific surface area, pore volume and pore diameter of the catalyst Ni / HAC-600-700 are 2373 m 2 / g, 1.31 cm 3 / g and 2.20 nm. It can be seen from the table that different carbonization temperatures and activation temperatures have a significant effect on the pore distribution of HACs. o C) At the same time, as the activation temperature increases, the SSA of HAC-600-Y will first increase from 458 m 2 / g increased to 2373 m 2 / g, and then it will drop to 1949 m 2 / g. At the activation temperature (700 o C) are the same, there will be the same trend. This may be because as the carbonization temperature increases, the carbon structure will become denser and denser, and the rearrangement of the carbon skeleton and the shrinkage of the pores in the carbon structure will be unfavorable for the next step of activation. This is also consistent with the fact that when the activation temperature is the same, the specific surface area of HAC shows a trend of first increasing and then decreasing with the increase of carbonization temperature.
[0024] Figure 1 (a) and Figure 1 (b) are XRD patterns of different catalysts prepared in Example 1. As shown in Figure 1, when the carbonization temperature and activation temperature of HAC are relatively low (Ni / HAC-400-400, Ni / HAC-500-500), the carbonization temperature of HAC is 44.51°, while the activation temperature of HAC is 400°. o ,51.85 o and 76.37 o The three typical diffraction peaks of the catalyst are shown in Figure 1, which correspond to the (111), (200) and (220) crystal planes of Ni. The diffraction peaks of the Ni / HAC-600-700 catalyst are broad and slow, indicating that the metal is highly dispersed on the support surface and the metal particles are small in size.
[0025] Figure 2 is the contact angle diagram of different catalysts obtained in Example 1, such as Figure 2 As shown in Figure 2, the average contact angles of Ni / HAC-400-400, Ni / HAC-600-700, Ni / HAC-700-700 and Ni / HAC-900-900 are 131.80 o ,71.67 o ,83.93 o and 92.68 o This qualitatively represents the hydrophilicity of Ni / HACs at different carbonization temperatures and activation temperatures.
[0026] Figure 3 is the SEM image of different catalysts prepared in Example 1; Figure 3 It can be seen that metallic nickel is evenly distributed on the surface and in the pores of the Ni / HAC-600-700 catalyst, the metal particles are small and evenly dispersed, and the surface morphology of the carrier is relatively rough.
[0027] Figure 4 is a TEM image of different catalysts prepared in Example 1; Figure 4 (b) It can be seen that the metal Ni is evenly distributed in HAC-600-700. And because it has the largest specific surface area, only a few Ni NPs agglomerate into larger particles. The size distribution of NPs is between 2-15nm, with an average value of about 7.87nm. Figure 4 (a)-(d) It can be seen that compared with the other three catalysts (Ni / HAC-400-400, Ni / HAC-700-700, Ni / HAC-900-900), Ni / HAC-600-700 has the largest specific surface area, which makes the NPs more evenly dispersed on the surface of HAC-600-700 and the metal particle size smaller. This conclusion is consistent with the analysis results of XRD. Figure 4(e) is the high transmission electron microscopy (HRTEM) of Ni / HAC-600-700, where the lattice fringes with a spacing of 0.201 nm can be clearly seen, which matches the d spacing of the metal Ni crystal plane (111). This shows that the metal Ni on HAC-600-700 has a fairly high crystallinity. Figure 4 (f) EDS layered image of TEM test elements of Ni / HAC-600-700.
[0028] Comparative Example 1: Ni-based catalysts with different carriers Using deionized water as the impregnation liquid, different carriers including AC-1 (chemically pure activated carbon purchased from Xilong Chemical) and AC-2 (activated carbon model YP50F purchased from Kuraray) were selected to prepare the following two Ni-based catalysts by wet impregnation method, named Ni / AC-1 and Ni / AC-2, with a loading amount of 10 wt.%.
[0029] Table 2 Physical structure properties of catalysts a The specific surface area was calculated according to the BET method. b The total pore volume is calculated at a relative pressure of P / P0=0.99 c The average pore size is calculated according to the BJH method. Example 2: Application of catalytic hydrolysis of lignite model compounds All catalytic reactions were carried out in a 100 mL stainless steel autoclave.
[0030] The reactants diphenyl ether (100 mg), Ni-based catalyst (50 mg) and isopropanol (20 mL) were placed in the reactor. After sealing, the remaining air was removed by passing hydrogen three times. Subsequently, the reactor was pressurized with hydrogen to the desired pressure (0.5-3.0 MPa) at room temperature. The temperature was then raised to the desired reaction temperature (120-220 o C) and maintained at a vigorous stirring speed of 800 rpm for a certain period of time (30-150 min). After the experiment, the reaction system was naturally cooled to room temperature and the pressure was released. The reaction mixture was filtered to remove the catalyst, and the obtained organic phase was analyzed by gas chromatography-mass spectrometry (GC-MS) and gas chromatography (GC).
[0031] The experimental results show that the three catalysts Ni / AC-1, Ni / AC-2 and Ni / HAC-600-700 can achieve complete conversion of diphenyl ether. The order of the three catalysts for the hydrogenation and hydrolysis of diphenyl ether is: Ni / HAC-600-700>Ni / AC-2>Ni / AC-1. It is worth noting that when AC-1 is used as a carrier, the selectivity of cyclohexanol is as low as 47.6%. In addition, when AC-2 and HAC-600-700 are used as carriers, although the selectivity of cyclohexanol is similar, the hydrolysis ratio of Ni / HAC-600-700 is still better than Ni / AC-2, and because HAC prepared from glucose is cheap and widely available, HAC-600-700 is a better choice than AC-2. According to the above analysis, Ni / HAC-600-700 prepared by HAC-600-700 has the highest catalytic hydrolysis activity.
[0032] Table 3 Catalytic performance of different catalysts for diphenyl ether hydrogenation and hydrolysis Reaction conditions: 100 mg diphenyl ether, 50 mg catalyst, 20 mL isopropanol, 180 o C, 1 MPa H2, 2 h Example 3: Ni-based catalysts for hydrogenation and hydrolysis of different model compounds In order to further verify the hydrogenation and hydrolysis activity of Ni / HAC-600-700 catalyst, more lignite model compounds were selected for reaction, and the hydrogenation and hydrolysis conversion effects are listed in Table 3 below. The experimental results show that Ni / HAC-600-700 can almost completely convert diphenyl ether (serial number 1), 4-phenoxyphenol (serial number 2), p-xylyl ether (serial number 3), 4,4' dihydroxy diphenyl ether (serial number 4), benzyl phenyl ether (serial number 5), phenethyl phenyl ether (serial number 6) and dibenzyl ether (serial number 7) into the corresponding monocyclic products. Among them, for the model compounds 4-phenoxyphenol and 4,4' dihydroxy diphenyl ether with similar carbon numbers to diphenyl ether, Ni / HAC-600-700 can be highly selectively converted into alcohol compounds. As expected, Ni / HAC-600-700 can achieve complete conversion of these lignite derivatives under mild conditions, which shows that it has wide applicability.
[0033] Table 4 Effect of Ni / HAC-600-700 catalyst on hydrolysis of different lignite model compounds Example 4: Effect of Ni catalysts prepared with HACs supported at different carbonization and activation temperatures on hydrogenation and hydrolysis of diphenyl ether Reaction conditions: 100 mg diphenyl ether, 50 mg catalyst, 20 mL isopropanol, 2 h, 1 MPa H2 As shown in Figure 5 (a) to Figure 5 (c), the three graphs screened out the best carbonization temperature (600 o C) and activation temperature (700 o C). The catalysts with HACs with higher carbonization and activation temperatures as carriers all produce cyclohexane and cyclohexanol as the main products. Among them, although Ni / HAC-600-700 and Ni / HAC-700-700 can completely convert DPE, Ni / HAC-700-700 with relatively poor hydrophilicity will produce less cyclohexanol than Ni / HAC-600-700. It is worth noting that the selectivity of cyclohexanol of both is significantly higher than that of cyclohexane, which is because some diphenyl ether will be hydrolyzed to phenol, and phenol will be further hydrogenated to produce cyclohexanol. The hydrolysis ratios of the two are 32.3% and 27.9%, respectively.
[0034] Example 5: Effect of process conditions on diphenyl ether hydrogenation hydrolysis Reaction conditions: 100 mg diphenyl ether, 50 mg catalyst, 20 mL isopropanol, 180 o C, 2 h.
[0035] like Figure 6 As shown, at 160 o C, Ni / HAC-600-700 can achieve 100% conversion. The reaction temperature ranges from 120 o C up to 180 o C, the selectivity of the target product showed a trend of gradual increase, and at 180 o C. However, if the temperature is further increased, on the one hand, cyclohexanol may continue to dehydroxylate to form cyclohexane, and on the other hand, high temperature may promote the cleavage of CO bonds in DPE to form phenol and benzene, and benzene and phenol will be further hydrogenated to cyclohexanol and cyclohexane. In this process, the proportion of hydrogenated products is constantly decreasing, and the proportion of monocyclic products is constantly decreasing, which indicates that high temperature is conducive to the conversion of CPE into monocyclic products (cyclohexanol and cyclohexane), while at lower temperatures, it is more conducive to the formation of hydrogenated products.
[0036] Reaction time is another important parameter affecting the catalytic hydrogenation and hydrolysis of DPE. The effect of time on the catalytic reaction of DPE is as follows: Figure 7 As shown, at 180 oC, the reaction time is 1 h, and the conversion rate can reach 100% and the selectivity is close to 60%. As time goes on, the cyclohexanol will increase slightly and then decrease. This may be because a small amount of DPE hydrogenation products will be further hydrolyzed to form cyclohexanol. As time goes on, a small amount of cyclohexanol will be dehydroxylated to form cyclohexane. This explains why the hydrolysis ratio will increase first and then decrease after the reaction reaches 1 h.
[0037] like Figure 8 As shown, the effect of reaction pressure on the catalytic effect of DPE. When the reaction pressure is in the pressure range of 0.5-3 MPa, the catalyst can achieve 100% conversion using Ni / HAC-600-700. As the pressure increases, the selectivity of cyclohexanol increases slightly, while cyclohexane tends to gradually decrease, resulting in a gradual increase in the hydrolysis ratio. This is because in previous studies, it has been proposed that DPE may undergo three reactions first, namely hydrogenolysis, hydrolysis, and hydrogenation (direct hydrogenation of aromatic rings). Combined with the effect of pressure on diphenyl ether in the catalytic conversion process in this study, it can be inferred that after the pressure gradually increases, DPE will preferentially hydrogenate the aromatic rings, and then reductive hydrolysis, which may also be the reason why cyclohexanol will have an upward trend. Since the hydrolysis ratio did not increase significantly after the reaction pressure reached 1 MPa, considering the actual economic benefits, the optimal reaction pressure was selected as 1 MPa.
Claims
1. A method for preparing a hydrophilic nickel-carbon catalyst having catalytic hydrolysis performance, characterized in that: The steps include: In the first step, glucose was placed in a tube furnace under an inert atmosphere at 400-900 o C for 2 h; the carbon obtained by carbonization was ground into powder, and then subjected to alkali washing, acid washing, water washing and drying treatment in sequence to obtain a glucose-based carbon material; the glucose-based carbon material was fully mixed with potassium hydroxide in a mass ratio of 1:3, and then the mixture was placed in a tube furnace and heated at 400-900 o C for 2 h; the activated sample was acid washed, water washed and dried in sequence to obtain the HAC carrier; In the second step, the HAC carrier is added to the nickel salt aqueous solution and ultrasonically dispersed, and then the mixed solution is vacuum impregnated at room temperature for 24 hours. The impregnated mixture is dried and then calcined in an inert atmosphere at 450°C for 2 hours, and then reduced in a reducing atmosphere at 450°C for 2 hours to obtain a hydrophilic nickel-carbon catalyst.
2. The method for preparing a hydrophilic nickel-carbon catalyst having catalytic hydrolysis performance according to claim 1, characterized in that: In the first step, the carbonization temperature is 600 o C, the activation temperature is 700 o C.
3. The method for preparing a hydrophilic nickel-carbon catalyst having catalytic hydrolysis performance according to claim 1, characterized in that: In the second step, the nickel salt is one of nickel nitrate, nickel acetate, nickel sulfate and nickel chloride.
4. The method for preparing a hydrophilic nickel-carbon catalyst having catalytic hydrolysis performance according to claim 1, characterized in that: In the second step, the heating rate of the calcination and reduction is maintained at 15 o C / min.
5. A hydrophilic nickel-carbon catalyst having catalytic hydrolysis performance, characterized in that: The method is prepared according to any one of claims 1 to 4.
6. A hydrophilic nickel-carbon catalyst having catalytic hydrolysis performance according to claim 5, characterized in that: The nickel loading in the catalyst is 10 wt.%.
7. Use of the hydrophilic nickel-carbon catalyst according to claim 5 or 6 in catalytic hydrogenation and hydrolysis of lignite model compounds.
8. The use according to claim 7, characterized in that: The specific application steps include: The substrate, nickel-carbon catalyst and isopropanol are placed in a reactor, which is sealed and then the remaining air is removed by passing hydrogen. Subsequently, the reactor is pressurized to 0.5-3.0 MPa with hydrogen at room temperature, and then the temperature is raised to the desired reaction temperature of 120-220 °C. o C, and maintained at a vigorous stirring speed of 800 rpm for 30-150 min; after the experiment, the reaction system was naturally cooled to room temperature and the pressure was released. The reaction mixture was filtered to remove the catalyst, and the obtained organic phase was analyzed by gas chromatography-mass spectrometry and gas chromatography.
9. The use according to claim 8, characterized in that: The substrates are diphenyl ether, 4-phenoxyphenol and 4,4'-dihydroxydiphenyl ether.
Citation Information
Patent Citations
Porous active charcoal material supporting cobalt nanoparticle material, preparation method, and application thereof
CN107159214A
Application of nickel-based catalyst with high-specific-surface-area hydrophilic activated carbon as carrier in catalytic hydrogenation hydrolysis
CN113083308A
Nickel-carbon catalyst with high specific surface area and preparation method and application thereof
CN113145121A
Producing Method of Ni / Activated Carbon Catalysts and Hydrogen-Producing System through Supercritical Water Gasification of Organic Compounds using Ni / Activated Carbon Catalysts and Driving M ...
KR100780910B1
Nanocarbon-activated carbon composite
US20090220767A1